2019
DOI: 10.1158/2326-6066.cir-18-0725
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TIGIT/CD155 Signaling Reverses T-cell Exhaustion and Enhances Antitumor Capability in Head and Neck Squamous Cell Carcinoma

Abstract: Immunosuppression is common in head and neck squamous cell carcinoma (HNSCC). In previous studies, the TIGIT/CD155 pathway was identified as an immunecheckpoint signaling pathway that contributes to the "exhaustion" state of infiltrating T cells. Here, we sought to explore the clinical significance of TIGIT/CD155 signaling in HNSCC and identify the therapeutic effect of the TIGIT/CD155 pathway in a transgenic mouse model. TIGIT was overexpressed on tumor-infiltrating CD8 þ and CD4 þ T cells in both HNSCC patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 44 publications
6
115
1
Order By: Relevance
“…Nevertheless, the majority of patients still progress even though tumour response was observed early in ICB antitumor therapy, suggesting that some other immunosuppressors and/or pathways complement the inactivation of PD-1 and CTLA-4. Recently, TIM339 and TIGIT40 have been shown to contribute to T-cell exhaustion, and co-blockade of two pathways (PD-1 and TIM3 or PD-1 and TIGIT) is more effective in restoring T cell proliferation and cytokine production 41–43. Here, we found that in addition to PD-L1/PD-L2 and CTLA-4, TIM3 and TIGIT also had much higher expression levels in the MSI-H1 subgroup (figure 4B).…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, the majority of patients still progress even though tumour response was observed early in ICB antitumor therapy, suggesting that some other immunosuppressors and/or pathways complement the inactivation of PD-1 and CTLA-4. Recently, TIM339 and TIGIT40 have been shown to contribute to T-cell exhaustion, and co-blockade of two pathways (PD-1 and TIM3 or PD-1 and TIGIT) is more effective in restoring T cell proliferation and cytokine production 41–43. Here, we found that in addition to PD-L1/PD-L2 and CTLA-4, TIM3 and TIGIT also had much higher expression levels in the MSI-H1 subgroup (figure 4B).…”
Section: Discussionsupporting
confidence: 54%
“…[197][198][199][200] Currently, a number of clinical studies are investigating the therapeutic impact of TIGIT blockade either alone or in combination with PD-1 in multiple cancer types. 196,201,202 The checkpoint receptor LAG-3 holds great potential in cancer immunotherapy. LAG-3 is expressed widely in tumor-infiltrating lymphocytes in various tumors.…”
Section: T-cell Exhaustion In Cancermentioning
confidence: 99%
“…While peritumoral CD8 + TILs may indicate an adaptive immune response, studies have shown that dysfunctional TILs are commonly present, which exhibit decreased cytokine production and proliferation ability and lack of cytotoxic functions 24,25 . Exhausted and dysfunctional TILs in HNSCC cases have been characterized by the upregulation of several checkpoint markers, such as programmed cell death 1 (PD‐1), lymphocyte‐activation gene 3 (LAG‐3), T cell immunoglobulin mucin protein‐3 (TIM‐3), cytotoxic T lymphocyte–associated protein 4 (CTLA‐4), and 2B4 26–29 (Figure 1). The cause and mechanisms by which the T cells become exhausted and dysfunctional in HNSCCs are discussed in detail below.…”
Section: T Cellsmentioning
confidence: 99%